Mobile phones and computer keyboards: unlikely reservoirs of multidrug-resistant organisms in the tertiary intensive care unit. Issue 3 (July 2018) - Smibert, O.C.; Aung, A.K.; Woolnough, E.; Carter, G.P.; Schultz, M.B.; Howden, B.P.; Seemann, T.; Spelman, D.; McGloughlin, S.; Peleg, A.Y.
Summary: Few studies have used molecular epidemiological methods to study transmission links to clinical isolates in intensive care units. Ninety-four multidrug-resistant organisms (MDROs) cultured from routine specimens from intensive care unit (ICU) patients over 13 weeks were stored (11 meticillin-resistant Staphylococcus aureus (MRSA), two vancomycin-resistant enterococci and 81 Gram-negative bacteria). Medical staff personal mobile phones, departmental phones, and ICU keyboards were swabbed and cultured for MDROs; MRSA was isolated from two phones. Environmental and patient isolates of the same genus were selected for whole genome sequencing. On whole genome sequencing, the mobile phone isolates had a pairwise single nucleotide polymorphism (SNP) distance of 183. However, >15, 000 core genome SNPs separated the mobile phone and clinical isolates. In a low-endemic setting, mobile phones and keyboards appear unlikely to contribute to hospital-acquired MDROs.